A new goatfish species of the genus Upeneus (Mullidae) in the Gulf of Antalya - Gökoğlu, Mehmet (Acta Aquatica: Aquatic Sciences Journal, 2018)
During the night diving in the Gulf of Antalya, a different type of mullidae member was seen. This fish was determined that this species is Upeneus tragula. There are two species of fish belonging to the Upeneus genus Mullidaein the Mediterranean. With the addition of Upeneus tragula to these fishes, the number of Upeneus genus in the Mediterranean has increased to three.Keywords: Upeneus tragula; Gulf of Antalya; Coast of Turkey; Mediterranean